Risk factors for periventricular echodensities and outcomes in preterm infants. (16th February 2017) - Kolnik, Noga; Strauss, Tzipora; Globus, Omer; Leibovitch, Leah; Schushan-Eisen, Irit; Morag, Iris; Maayan-Metzger, Ayala
Abstract: Objectives : To determine the incidence, risk factors and outcomes associated with transient and/or persistent periventricular echodensities (PVED) among preterm infants. Methods : Medical records of preterm infants born at ≤ 32 weeks gestational age (GA) with PVED and no other brain pathology were reviewed and compared to matched control infants in a case-controlled retrospective study. Neurodevelopmental outcomes at 8–24 months corrected age were documented. Results : A 17.8% incidence of PVED was recorded, with the highest incidence of 30–40% recorded at 29–31 weeks GA. Study and control groups were similar for all maternal parameters and neonatal morbidities, except for a higher incidence of respiratory distress syndrome among the study group. PVED at one month of age was predicted by 5 min Apgar score < 7 [OR = 33.78 (CI 2.94–388.06, p = 0.005)]. PVED was not associated with long-term neurodevelopmental disability. Conclusions : No risk factors or specific associated morbidities were identified among preterm infants with transient PVED. PVED at one month of age was predicted by low 5 min Apgar scores, possibly suggesting different pathogenesis or timing between the groups. Long-term outcome studies are needed to determine PVED impact.